Proceedings of the 46th ACM Technical Symposium on Computer Science Education 2015
DOI: 10.1145/2676723.2677230
|View full text |Cite
|
Sign up to set email alerts
|

Language Migration in non-CS Introductory Programming through Mutual Language Translation Environment

Abstract: In the past decade, improvements have been made to the environments used for introductory programming education, including by the introduction of visual programming languages such as Squeak and Scratch. However, migration from these languages to text-based programming languages such as C and Java is still a problem. Hence, using the OpenBlocks framework proposed at the Massachusetts Institute of Technology, we developed a system named BlockEditor, which can translate bidirectionally between Block (the block la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 15 publications
1
25
1
2
Order By: Relevance
“…Experimentally, we did see users deploy both modes, and seem to understand the connection between the two. Similar to DiSalvo [49], and like Weintrop [50] and Matsuzawa [20] as well, however, we found that a number of participants very strongly preferred the textual mode and were even scornful of the tiled mode and its presence, to the point of using text almost exclusively even when the system design made it more difficult to complete tasks in that way. Three participants explicitly noted unprompted that they were predisposed to dislike GUIs.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Experimentally, we did see users deploy both modes, and seem to understand the connection between the two. Similar to DiSalvo [49], and like Weintrop [50] and Matsuzawa [20] as well, however, we found that a number of participants very strongly preferred the textual mode and were even scornful of the tiled mode and its presence, to the point of using text almost exclusively even when the system design made it more difficult to complete tasks in that way. Three participants explicitly noted unprompted that they were predisposed to dislike GUIs.…”
Section: Discussionsupporting
confidence: 83%
“…In our experiment, which used exactly parallel languages in both textual and visual modes, and in Matsuzawa et al's [20], which did not, understanding the relation between the two did not seem to be an especial problem, but intimidation by text was evident. Students in Matsuzawa et al's study with lower self-rating of their skill avoided the text view, but none of our self-rating questions showed a strong correlation with use of either mode; we did not have a generic "rate your programming skill" question, however.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations